Smart marketing and advanced personalization in healthcare services: the role of consumer data in improving patient experience and brand interaction - Tarassoli , Mehrdad; Ashouri, Mohammad Farid (Social Determinants of Health, 2025)
Background: With the expansion of digital technologies in healthcare, smart marketing has emerged as a data-driven approach that plays a prominent role in enhancing patient experience and improving interaction with healthcare service brands. Methods: This descriptive-analytical study was conducted in a field setting. The study population consisted of 220 managers and experts in healthcare marketing from healthcare institutions and health-focused companies. Using Cochran’s formula, a simple random sample of 140 participants was selected. The data collection tool was a researcher-developed questionnaire, whose validity was confirmed by digital health experts and reliability was verified with a Cronbach’s alpha of 0.87. Data analysis was performed using SPSS software and multiple regression analysis. Results: The Results showed that smart marketing significantly and positively influences patient (customer) experience, explaining approximately 62% of its variance (β = 0.55, p < 0.01). Additionally, brand interaction contributed to 56% of the changes in patient experience (β = 0.44, p < 0.01), while the use of consumer data accounted for 22% of its variation (β = 0.81, p < 0.01). Furthermore, patient experience itself explained 28% of the variance in advanced Personalization, confirming its mediating role in enhancing personalize healthcare delivery. Conclusion: Data-driven smart marketing in healthcare can facilitate the design of personalized healthcare services, leading to sustainable patient interactions and gaining a competitive advantage in the healthcare market.